2015
DOI: 10.1021/acs.organomet.5b00413
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Heteroscorpionate Zwitterionic Zinc Terminal Hydride: Synthesis, Reactivity, and Catalysis for Hydrosilylation of Aldehydes

Abstract: Treatment of heteroscorpionate zinc benzyloxy complex LZnOBn (1, L = ( Me Pz) 2 CP(Ph) 2 NPh, Me Pz = 3,5-dimethylpyrazolyl) with phenylsilane (PhSiH 3 ) gave a zinc hydride complex LZnH (2) containing a rare terminal hydride fragment. X-ray diffraction analysis and the DFT calculation confirm the zwitterionic structure of complex 2. The stoichiometric reaction of 2 with CS 2 readily afforded a dithioformate complex LZnSCH(S) (3) of the CS insertion into the Zn−H product. Moreover, complex 2 was an efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Heteroscorpionate zinc hydride complex 1 (Chart S1, Supporting Information) was identified as an efficient catalyst in the hydrosilylation of aldehyde at room temperature without any byproduct or change of pH value . The reaction conditions were rather mild to inhibit any side reactions and the catalyst exhibited excellent tolerance to the functiontional groups.…”
Section: Resultsmentioning
confidence: 99%
“…Heteroscorpionate zinc hydride complex 1 (Chart S1, Supporting Information) was identified as an efficient catalyst in the hydrosilylation of aldehyde at room temperature without any byproduct or change of pH value . The reaction conditions were rather mild to inhibit any side reactions and the catalyst exhibited excellent tolerance to the functiontional groups.…”
Section: Resultsmentioning
confidence: 99%
“…based catalysts are highly desirable. [11][12][13][14] For example, Gerard Parkin et al reported that {[κ 3 -Tptm]M}[HB(C 6 F 5 ) 3 ] catalytic systems could efficiently catalyze a CO 2 hydrosilylation reaction, in which a magnesium-based complex showed efficient capability for the CO 2 reduction reaction. 15 Catalytic hydroboration of CO 2 is an alternative method for efficiently transforming CO 2 to valuable compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular zinc compounds have received prominence as reagents for the reduction of unsaturated bonds. [1][2][3][4] They are employedi nt he reduction of olefins, [5][6][7][8] imines, [9][10][11] aldehydes, ketones, [12][13][14][15][16][17][18] and carbond ioxide. [19][20][21][22][23][24][25][26][27][28][29][30] Catalyticr eductiono f carbon dioxide through catalytic hydrosilylation [31][32][33][34] and, to some extent, hydroboration [35,36] with zinc catalysts has been investigated.…”
Section: Introductionmentioning
confidence: 99%